2022
DOI: 10.1021/acsami.2c10471
|View full text |Cite
|
Sign up to set email alerts
|

In/Ce Co-doped Li3VO4 and Nitrogen-modified Carbon Nanofiber Composites as Advanced Anode Materials for Lithium-ion Batteries

Abstract: Li 3 VO 4 (LVO) is considered as a novel alternative anode material for lithium-ion batteries (LIBs) due to its high capacity and good safety. However, the inferior electronic conductivity impedes its further application. Here, nanofibers (nLICVO/NC) with In/Ce co-doped Li 3 VO 4 strengthened by nitrogen-modified carbon are prepared. Density functional theory calculations demonstrate that In/Ce co-doping can substantially reduce the LVO band gap and achieve orders of magnitude increase (from 2.79 × 10 −4 to 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…4,50 The reduction peaks moving to about 0.6 and 1.0 V after three cycles resulted from the electrochemical activation of the Li 3 VO 4 @rGO–R electrode. 51 Correspondingly, the oxidation peaks at 1.05 and 1.32 V during the anodic scan correlate with the deintercalation of Li + from Li 3 VO 4 . 38 The galvanostatic discharge/charge (GCD) profiles of Li 3 VO 4 @rGO–R at 0.1 A g −1 are shown in Fig.…”
Section: Resultsmentioning
confidence: 79%
“…4,50 The reduction peaks moving to about 0.6 and 1.0 V after three cycles resulted from the electrochemical activation of the Li 3 VO 4 @rGO–R electrode. 51 Correspondingly, the oxidation peaks at 1.05 and 1.32 V during the anodic scan correlate with the deintercalation of Li + from Li 3 VO 4 . 38 The galvanostatic discharge/charge (GCD) profiles of Li 3 VO 4 @rGO–R at 0.1 A g −1 are shown in Fig.…”
Section: Resultsmentioning
confidence: 79%
“…4i). 18,26,[46][47][48][49][50][51][52][53][54][55] The EIS tests of these electrodes were also measured aer 10 000 cycles as shown in Fig. S15a.…”
Section: Resultsmentioning
confidence: 99%
“…[127,128] Li et al reported a simple strategy to fabricate nitrogen, sulfur, and dual metal (Fe/Ni) co-doped carbon nanocomposite as an effective bifunctional catalyst for RZABs. [96] First, 1,4-bis(1-hexy-1Himidazo-[4,5-f ] [1,10] phenanthroline-2-yl) benzene (HIPB) compounds were synthesized and used as organic ligands to generate TM-mediated imidazole-o-phenanthroline derivatives (labeled as HIPB-M). HIPB-M was mixed with trithiocyanuric acid (TTCA) and pyrolyzed at a high temperature to obtain FeNi/NS-C electrocatalyst.…”
Section: Co-n-c Smcs With δE Between 07 and 09 Vmentioning
confidence: 99%
“…Lithium‐ion batteries (LIBs) have been the most successful portable energy storage technology since they were first reported in 1990. [ 1,2 ] Despite the great commercial success of LIB technology, it still suffers from insufficient energy density (typically less than 350 Wh kg −1 ) the high cost of anode materials, and potential safety issues. [ 3,4 ] Therefore, there is a need to find safer, more efficient, and cost‐effective solutions for energy conversion and storage.…”
Section: Introductionmentioning
confidence: 99%